SUPERVISI TENAGA PENDIDIKAN BAHASA INDONESIA DALAM MENINKATKAN KINERJA GURU DI MTS NEGERI2 PROBOLINGGO - Moh. Alex Arifin; Unaisatuz Zahro; Hemas Haryas Harja Susetya (Universitas Muhammadiyah Surabaya, 2025)
Learning supervision plays an important role in improving teacher performance during the learning process, but there are still few studies that discuss in depth the relationship between a serious and disciplined teacher teaching style and the results of quantitative learning observations. This study aims to determine the implementation of learning by a teacher who is known to have a firm teaching character, through a supervision instrument consisting of 46 indicators. The method used in this study is descriptive qualitative with data collection techniques through direct observation carried out at MTs Negeri 2 Probolinggo. The results of the observation showed that the teacher implemented 42 of the 46 learning indicators with an achievement percentage of 91.30% which is included in the very good category. This finding shows that a serious teaching style does not always have a negative impact on collaborative learning, as long as learning strategies and approaches are implemented professionally and systematically. This study contributes to the practice of educational supervision by emphasizing the importance of data-based evaluation to support teacher training fairly and objectively.